Optimizing Village Fund Allocation through Strengthening Leadership and Institutions in the Midst of Local Political Constraints Case Study of Village Governance in West Java, Indonesia - Fauzi, Fahmi; Kania, Ikeu (ann4publisher@gmail.com, 2026)
Background. The management of village funds in Indonesia has become an important foundation in strengthening community-based development. However, in practice, the effectiveness of budget allocation often faces complex local challenges. Purpose. This study aims to examine how village head leadership and local institutional strength can encourage the optimization of the use of village funds amid political pressure stemming from local rivalry after the village head election. This study was conducted in Mekarsari Village, Selaawi District, Garut Regency, a village with economic characteristics of the community that is mostly engaged in bamboo weaving crafts and has a strong social structure but is vulnerable to political polarization. Method. Using a qualitative approach with the main method of documentation study, this study utilizes official documents, namely RPJMDes, RKPDes, APBDes, and village deliberation minutes. Interviews are only conducted on a limited basis to strengthen the interpretation of document data. Result. The results of the analysis show that even though the village head has prepared a development plan according to the applicable rules and stages, the implementation of the program has faced obstacles by political resistance and subjective perceptions from some communities. However, strengthening participatory and transparent village institutions is able to withstand this pressure and maintain the direction of village development in accordance with the medium-term vision contained in the RPJMDes. Conclusion. This study recommends the need for a local political management strategy based on open dialogue and the strengthening of village institutions as a protector against short-term conflicts of interest. Implementation. These findings contribute to the village governance literature and demonstrate the importance of a balance between leadership, institutions, and local dynamics in village fund management.